Bioinspired Hybrid White Light-Emitting Diodes - Weber, Michael; Niklaus, Lukas; Pröschel, Marlene; Brana Coto, Pedro; Sonnewald, Uwe; Costa Riquelme, Rubén Dario (Advanced Materials, 2015)
The first bioinspired hybrid white-light-emitting diodes (bio-HLEDs) featuring protein cascade coatings are presented. For easy fabrication a new strategy to stabilize proteins in rubber-like material was developed. The synergy between the excellent features of fluorescent proteins and the easily processed rubber produces bio-HLEDs with less than 10% loss in luminous efficiency over 100 hours.

Charge Transport in C60-based Single-Molecule Junctions with Graphene Electrodes - Leitherer, Susanne; Brana Coto, Pedro; Ullmann, Konrad; Weber, Heiko B.; Thoss, Michael (Nanoscale, 2017)
We investigate charge transport in C60-based single-molecule junctions with graphene electrodes employing a combination of density functional theory (DFT) electronic structure calculations and Landauer transport theory. In particular, the dependence of the transport properties on the conformation of the molecular bridge and the type of termination of the graphene electrodes is investigated. Furthermore, electron pathways through the junctions are analyzed using the theory of local currents. The results reveal, in agreement with previous experiments, a pronounced dependence of the transport properties on the bias polarity, which is rationalized in terms of the electronic structure of the molecule. It is also shown that the edge states of zigzag-terminated graphene induce additional transport channels, which dominate transport at low voltages. The importance of the edge states for transport depends profoundly on the interface geometry of the junctions.

Charge Transport in Pentacene–Graphene Nanojunctions - Pshenichnyuk, Ivan; Brana Coto, Pedro; Leitherer, Susanne; Thoss, Michael (Journal of Physical Chemistry Letters, 2013)
We investigate charge transport in pentacene-graphene nanojunctions employing density functional theory (DFT) electronic structure calculations and the Landauer transport formalism. The results show that the unique electronic properties of graphene strongly influence the transport in the nanojunctions. In particular, edge states in graphene electrodes with zigzag termination result in additional transport channels close to the Fermi energy, which deeply affects the conductance at small bias voltages. Investigating different linker groups as well as chemical substitution, we demonstrate how the transport properties are furthermore influenced by the molecule-lead coupling and the energy level lineup. © 2013 American Chemical Society.
UnivIS-Import:2015-04-14:Pub.2013.nat.dphy.ITP.ppem.charge
Keywords: Energy and Charge Transport; Energy Conversion and Storage

Dynamical Simulation of Electron Transfer Processes in Alkanethiolate Self-Assembled Monolayers at the Au(111) Surface - Prucker, Veronika; Rubio-Pons, Oscar; Bockstedte, Michel Georg; Wang, Haobin; Brana Coto, Pedro; Thoss, Michael (Journal of Physical Chemistry C, 2013)
Electron transfer is investigated in a series of self-assembled monolayers (SAMs) consisting of nitrile-substituted short chain alkanethiolate molecules adsorbed at the Au(111) surface. Using first-principles methods and a model electron transfer Hamiltonian, we analyze the main factors controlling, at the molecular level, the electron injection times from donor states localized at the tail group of the SAM into the Au(111) substrate. We show that the donor-acceptor electronic couplings depend significantly on the orbital symmetry of the donor state and the length of the aliphatic spacer chain of the SAM. The dependence on the donor state symmetry and on the molecular structure of the linker can be used to control the electron injection times even in situations where the energy separation between the donor states is smaller than their width. © 2013 American Chemical Society.
UnivIS-Import:2015-04-14:Pub.2013.nat.dphy.ITP.ppem.dynami

Easy and versatile coating approach for long-living white hybrid light-emitting diodes - Niklaus, Lukas; Dakhil, Haider; Kostrzewa, Monika Maria; Brana Coto, Pedro; Sonnewald, Uwe; Wierschem, Andreas; Costa Riquelme, Rubén Dario (Materials Horizons, 2016)
Herein, we provide a new easy-to-do protocol for preparing luminescent rubber-like materials based on a wide palette of compounds, such as small-molecules, quantum dots, polymers, and coordination complexes. The combination of this new protocol with that for preparing similar rubbers based on fluorescent proteins states the universal character of our approach. This is further assessed by using comprehensive spectroscopic and rheological investigations. Furthermore, the novel luminescent rubbers are applied as downconverting packing systems to develop white hybrid light-emitting diodes (WHLEDs), which are heralded as a solid alternative to achieve energy-saving, solid-state, and white-emitting sources in the coming future. As such, the current work also provides a clear prospect of this emerging lighting technology by means of a direct comparison among WHLEDs fabricated with all the above-mentioned down-converting systems. Here, the use of rubbers based on coordination complexes outperforms the others in terms of both luminous efficiency and colour quality with an unprecedented stability superior to 1000 h under continuous operation conditions. This represents an order of magnitude enhancement compared to the state-of-the-art WHLEDs, while keeping luminous efficiencies of around 100 lm W-1.

Electroluminescence: From White to Red: Electric-Field Dependent Chromaticity of Light-Emitting Electrochemical Cells based on Archetypal Porphyrins (Adv. Funct. Mater. 37/2016) - Weber, Michael; Wittmann, Judith; Burger, Alexandra; Malcioglu, Osman; Segarra-Martí, Javier; Hirsch, Andreas; Coto, Pedro B.; Bockstedte, Michel Georg; Costa, Ruben Dario (Advanced Functional Materials, 2016)
CRIS-Team Scopus Importer:2023-03-07
Keywords: collinear and vicinal regioisomers; electric-field dependent chromaticity; light-emitting electrochemical cells; tetraphenyl porphyrin; thin-film white-emitting sources

Evidence for Charge-Transfer Mediation in the Primary Events of Singlet Fission in a Weakly Coupled Pentacene Dimer - Basel, Bettina; Zirzlmeier, Johannes; Hetzer, Constantin; Seelam, Rajagopala Reddy; Phelan, Brian T.; Krzyaniak, Matthew D.; Volland, Michel; Brana Coto, Pedro; Young, Ryan M.; Clark, Timothy; Thoss, Michael; Tykwinski, Rik; et al. (Chem, 2018)
Singlet fission (SF) is a process that converts one singlet excited state into two triplet states. The mechanism of SF is still not well understood. Here, we report on the use of a combination of transient absorption and electron paramagnetic resonance spectroscopies in conjunction with theoretical calculations to probe SF in a pentacene dimer linked by a non-conjugated, 1,4-diethynylbicyclo[2.2.2]octane spacer. Next to observing the key intermediates in solution-based SF, including the formation and decay of a quintet state that precedes formation of the pentacene triplet excitons, we demonstrate that the coupling is sufficiently weak that SF is essentially inoperative in non-polar media. Transitioning to a polar medium, however, amplifies the coupling strength such that SF becomes operative and supports long triplet lifetimes. Our results offer strong evidence for a charge-transfer mediation and, in turn, provide a solid framework for decoding the complete mechanism of SF in systems beyond pentacene.

Experimental Evidence for Quantum Interference and Vibrationally Induced Decoherence in Single-Molecule Junctions - Ballmann, Stefan; Härtle, Rainer; Brana Coto, Pedro; Elbing, Mark; Mayor, Marcel; Bryce, Martin; Thoss, Michael; Weber, Heiko B. (Physical Review Letters, 2012)
We analyze quantum interference and decoherence effects in single-molecule junctions both experimentally and theoretically by means of the mechanically controlled break junction technique and density-functional theory. We consider the case where interference is provided by overlapping quasidegenerate states. Decoherence mechanisms arising from electronic-vibrational coupling strongly affect the electrical current flowing through a single-molecule contact and can be controlled by temperature variation. Our findings underline the universal relevance of vibrations for understanding charge transport through molecular junctions. © 2012 American Physical Society.
UnivIS-Import:2015-04-14:Pub.2012.nat.dphy.IAP.LAP.experi

Intermolecular Singlet Fission in Unsymmetrical Derivatives of Pentacene in Solution - Casillas Pacheco, Ruben; Adam, Matthias; Brana Coto, Pedro; Waterloo, Andreas; Zirzlmeier, Johannes; Reddy, Seelam Rajagopala; Hampel, Frank; Mcdonald, Robert; Tykwinski, Rik R.; Thoss, Michael; Guldi, Dirk Michael (Advanced Energy Materials, 2019)
Intermolecular singlet fission (SF) is an electronically coupled process between two chromophores, where distance dependences are decisive in terms of rates and yields. In the current work, a family of pentacene derivatives featuring different functional groups have been designed, synthesized, and probed with respect to intermolecular SF in the low, medium, and high concentration regimes rather than in the solid state. By means of advanced photophysical techniques, global analysis modeling, and ab initio calculations, a model for intermolecular SF is postulated. The model is based on an early key intermediate, which involves the diffusional encounter between one pentacene in its singlet excited-state with another one in its ground state and which features excimer characteristics. This is followed by a transformation into a coupled triplet excited-state. The role of the functional group appended to pentacene is analyzed with respect to steric shielding of the pentacene core as a means to prevent photophysical degradation, as well as control diffusional encounter and, subsequently, SF. The findings demonstrate the potential of new molecular materials for SF, especially in solution studies, as well as the challenges of implementing them in energy conversion schemes due to the appearance of photodegradation processes that compete with SF.
CRIS-Team WoS Importer:2019-02-21

Low-Lying Electronic Excited States of Pentacene Oligomers: A Comparative Electronic Structure Study in the Context of Singlet Fission - Brana Coto, Pedro; Sharifzadeh, Sahar; Neaton, Jeffrey B.; Thoss, Michael (Journal of Chemical Theory and Computation, 2015)
The lowest-lying electronic excited states of pentacene and its oligomers are investigated using accurate multireference wave function methods (CASPT2/CASSCF) and the many-body Greens’s function approach (GW/BSE). The results obtained for dimers and trimers of different geometry reveal a complex electronic structure, which includes locally excited, charge transfer, and multiexciton states. For singlets of single-excitation character, both approaches yield excitation energies that are in good overall quantitative agreement. While the multiexciton states are located relatively high in energy in all systems investigated, charge transfer states exist in close proximity to the lowest-lying absorbing states. The implications of the results for the mechanisms of singlet fission in pentacene are discussed.

Single-Molecule Junctions with Epitaxial Graphene Nanoelectrodes - Ullmann, Konrad; Brana Coto, Pedro; Leitherer, Susanne; Molina-Ontoria, Agustin; Martin, Nazario; Thoss, Michael; Weber, Heiko B. (Nano Letters, 2015)
On the way to ultraflat single-molecule junctions with transparent electrodes, we present a fabrication scheme based on epitaxial graphene nanoelectrodes. As a suitable molecule, we identified a molecular wire with fullerene anchor groups. With these two components, stable electrical characteristics could be recorded, Electrical measurements show that single-molecule junctions with graphene and with gold electrodes display a striking agreement. This motivated a hypothesis that the differential Conductance spectra are rather insensitive to the electrode material. It is further corroborated by the assignment of asymmetries and spectral features to internal molecular,degrees of freedom. The demonstrated open access graphene electrodes and the electrode-insensitive, molecules provide a model system that will allow for a thorough investigation of an individual single,molecule contact with additional probes.
Keywords: Epitaxial graphene nanoelectrodes; electroburning; single-molecule junctions; fullerene end groups; switching

Singlet fission in pentacene dimers - Zirzlmeier, Johannes; Lehnherr, Dan; Brana Coto, Pedro; Chernick, Erin; Casillas, Ruben; Basel, Bettina; Thoss, Michael; Tykwinski, Rik; Guldi, Dirk Michael (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Singlet fission (SF) has the potential to supersede the traditional solar energy conversion scheme by means of boosting the photon-to-current conversion efficiencies beyond the 30% Shockley-Queisser limit. Here, we show unambiguous and compelling evidence for unprecedented intramolecular SF within regioisomeric pentacene dimers in room-temperature solutions, with observed triplet quantum yields reaching as high as 156 ± 5%. Whereas previous studies have shown that the collision of a photoexcited chromophore with a ground-state chromophore can give rise to SF, here we demonstrate that the proximity and sufficient coupling through bond or space in pentacene dimers is enough to induce intramolecular SF where two triplets are generated on one molecule.

Solution-based intramolecular singlet fission in cross-conjugated pentacene dimers - Zirzlmeier, Johannes; Casillas, Ruben; Reddy, Rajagopala; Coto, Pedro B.; Lehnherr, Dan; Chernick, Erin; Papadopoulos, Ilias; Thoss, Michael; Tykwinski, Rik; Guldi, Dirk Michael (Nanoscale, 2016)
We show unambiguous and compelling evidence by means of pump-probe experiments, which are complemented by calculations using ab initio multireference perturbation theory, for intramolecular singlet fission (SF) within two synthetically tailored pentacene dimers with cross-conjugation, namely XC1 and XC2. The two pentacene dimers differ in terms of electronic interactions as evidenced by perturbation of the ground state absorption spectra stemming from stronger through-bond contributions in XC1 as confirmed by theory. Multiwavelength analysis, on one hand, and global analysis, on the other hand, confirm that the rapid singlet excited state decay and triplet excited state growth relate to SF. SF rate constants and quantum yields increase with solvent polarity. For example, XC2 reveals triplet quantum yields and rate constants as high as 162 ± 10% and (0.7 ± 0.1) × 1012 s-1, respectively, in room temperature solutions.
EAM Import::2019-03-13

Switching the conductance of a molecular junction using a proton transfer reaction - Hofmeister, Chriszandro; Härtle, Rainer; Rubio-Pons, Oscar; Brana Coto, Pedro; Sobolewski, Andrzej L.; Thoss, Michael (Journal of Molecular Modeling, 2014)
A novel mechanism for switching a molecular junction based on a proton transfer reaction triggered by an external electrostatic field is proposed. As a specific example to demonstrate the feasibility of the mechanism, the tautomers [2,5-(4-hydroxypyridine)] and 2,5-[4(1H)-pyridone] are considered. Employing a combination of first-principles electronic structure calculations and Landauer transport theory, we show that both tautomers exhibit very different conductance properties and realize the "on" and "off" states of a molecular switch. Moreover, we provide a proof of principle that both forms can be reversibly converted into each other using an external electrostatic field. © Springer-Verlag 2014.
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.ITP.ppem.switch
Keywords: Charge transport; Density functional theory; Molecular electronics; Molecular switch; Single molecule junction

The role of vibrations in single-molecule charge transport: A case study of oligoynes with pyridine anchor groups - Ballmann, Stefan Dieter; Hieringer, Wolfgang; Härtle, Rainer; Brana Coto, Pedro; Bryce, Martin; Görling, Andreas; Thoss, Michael; Weber, Heiko B. (physica status solidi (b), 2013)
We report on measurements on molecular wires in single-molecule junctions. The target is to identify vibrational signatures in the differential conductance spectra, which cannot be resolved for most molecular wires in the resonant transport regime. For the given molecules, we find indeed vibrational sidepeaks, which can be assigned to the longitudinal modes of the string-like central motif of the molecule by comparison with density functional theory. These data corroborate that oligoyne wires are ideally suited for characterizing vibrational sidepeaks. A current increase as a consequence of vibrational decoherence observed for thiols is, however, not found due to the pyridine anchor group chosen in the present molecules. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Unified model for singlet fission within a non-conjugated covalent pentacene dimer - Basel, Bettina; Zirzlmeier, Johannes; Hetzer, Constantin; Phelan, Brian T.; Krzyaniak, Matthew D.; Seelam, Rajagopala Reddy; Brana Coto, Pedro; Horwitz, Noah E.; Young, Ryan M.; White, Fraser J.; Hampel, Frank; Clark, Timothy; et al. (Nature Communications, 2017)
When molecular dimers, crystalline films or molecular aggregates absorb a photon to produce a singlet exciton, spin-allowed singlet fission may produce two triplet excitons that can be used to generate two electron-hole pairs, leading to a predicted similar to 50% enhancement in maximum solar cell performance. The singlet fission mechanism is still not well understood. Here we report on the use of time-resolved optical and electron paramagnetic resonance spectroscopy to probe singlet fission in a pentacene dimer linked by a non-conjugated spacer. We observe the key intermediates in the singlet fission process, including the formation and decay of a quintet state that precedes formation of the pentacene triplet excitons. Using these combined data, we develop a single kinetic model that describes the data over seven temporal orders of magnitude both at room and cryogenic temperatures.